ESG IN LIVING LABS: CORPORATE CO-CREATION FOR SUSTAINABLE INNOVATION (UKLO Proceedings, 2025)
Despite the increased interest in Environmental, Social, and Governance (ESG) and Corporate Social Responsibility (CSR) frameworks, companies face challenges in translating these commitments into impactful, community-centered, and scalable initiatives. This study explores the transformative potential of Living Labs—collaborative spaces for testing and refining innovations—to serve as an effective platform for incorporating ESG principles into corporate practices, resulting to meaningful sustainability outcomes. With the aim to investigate how living labs enable companies to co-create sustainable ESG projects with diverse stakeholders, fostering measurable environmental and social impact. The study takes a qualitative approach, examining ESG-focused Living Labs in Europe and Southeast Asia. Thematic analysis of ESG as a concept in Living Labs and reviews of project outcomes are used to understand how co-creation within Living Labs advances corporate ESG goals. Findings reveal that ESG initiatives developed through co-creation in Living Labs yield stronger stakeholder engagement, transparency, and scalability. Involving local communities, NGOs, and government entities in the design and implementation phases, companies achieve not only verifiable sustainability outcomes but also build trust and accountability in their ESG practices. Living Labs also provide companies with an environment to test and improve initiatives before wider implementation, effectively mitigating risks. The study concludes that Living Labs offers a dynamic and replicable model for companies aiming to advance ESG goals in diverse contexts. By embedding co-creation into their sustainability strategies, companies can make valuable contributions to sustainable development, offering a pathway for systemic change through responsible and inclusive innovation.